Nonregular Nanosystems Theory and Applications - Shunin, Yuri (Lecture Notes in Nanoscale Science and Technology,, 2018)
This book presents a systemic view of nanophenomena in terms of disordered condensed media with characteristics arising at various hierarchical levels from nanoagents/nanoparticles through multiple technological interfaces to the creation of micro- or mesostructures with essential nanodimensional effects. These properties can be seen in various schemes for the functionalization of nanocarbon systems, namely, CNTs, GNRs, GNFs, carbon-based nanoaerogels, nanofoams, and so on, where nonregularities characterize surface nanointeractions and various nanointerconnects, resulting in both predictable and unpredictable effects. Beginning with nanosensing and finishing with other forms of functionalized nanomaterials, these effects will define the prospective qualities of future consumer nanoproducts and nanodevices. This book covers all aspects of nonregular nanosystems arising from the fundamental properties of disordered nanosized media, from electronic structure, surface nanophysics, and allotropic forms of carbon such as graphene and fullerenes including defect characterization, to spintronics and 3D device principles. Nonregular Nanosystems will be of interest to students and specialists in various fields of nanotechnology and nanoscience, experts on surface nanophysics and nanochemistry, as well as managers dealing with marketing of nanoproducts and consumer behavior research.